2011
DOI: 10.1080/01924788.2011.625216
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Creative Expression Activities: The Links Between Creativity, Failure-Free, and Group Process With Levels of Staff-Participant Engagement and Participant Affect in an Adult Day Center

Abstract: The goal of this study was to assess the relationship between three characteristics identified as central to creative expression (CE) activities: creativity, failure-free, and group process with staff-participant engagement and participant affect. An observational study was conducted in an adult day center. Staff-participant interactions ( n = 241) were recorded as they participated in sculpture, which is a type of CE activity, and 12 different traditional activities. MANOVA tests revealed that levels of engag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This support comes from the need to create a sense of belonging to something (20) . A study conducted in adults and elderly in a day center observed higher positive affect levels in activities that included creativity or group process (23) .…”
Section: Discussionmentioning
confidence: 99%
“…This support comes from the need to create a sense of belonging to something (20) . A study conducted in adults and elderly in a day center observed higher positive affect levels in activities that included creativity or group process (23) .…”
Section: Discussionmentioning
confidence: 99%
“…In short, our students need to be given skills aimed at creative thinking and action. According to Rowe et al [1], creativity is a natural activity that determines how we can achieve something innovative or different through originality and flexibility. It is a natural, basic characteristic of the human mind that is potentially present in everyone, although different levels of creativity can be established, with some individuals being exceptionally gifted.…”
Section: Introductionmentioning
confidence: 99%